Antifungal activity and taxonomy of actinomyces strain 19G-317 - ZHANG Wu-gang; FENG Jun-tao; FANG Xiang-ling; XUE Quan-hong; ZHANG Xing (浙江大学学报. 农业与生命科学版)
The antifungal activity of actinomyces strain 19G-317 isolated from Sanjiangyuan National Nature Reserve was determined by confronting cultivation on PDA plates and potted plants, and the strain was identified by morphological, chemical and molecular methods. Results show that the strain displayed a broad - spectrum inhibitory activity to all the tested 23 plant pathogenic fungi, of which, the width of inhibition zones against 14 pathogens outweighed 10 mm, such as Botrytis cinerea, Sclerotinia sclerotiorum, Thanatephorus cucumeris, et al. Results of potted plants show that the protective and therapeutic efficacy of the fermentation broth to B. cirerea was 47.82% and 45.77%, respectively. According to the morphological, cultural, physiological and biochemical characteristics, and 16S rDNA sequence, the strain 19G-317 was identified as Streptomyces sp.